Dermcidin: a skeletal muscle myokine modulating cardiomyocyte survival and infarct size after coronary artery ligation. (22nd June 2015) - Esposito, Giovanni; Schiattarella, Gabriele Giacomo; Perrino, Cinzia; Cattaneo, Fabio; Pironti, Gianluigi; Franzone, Anna; Gargiulo, Giuseppe; Magliulo, Fabio; Serino, Federica; Carotenuto, Giuseppe; Sannino, Anna; Ilardi, Federica; et al.
Abstract: Aims: Coronary artery disease is the leading cause of death in western countries, and its association with lower extremity peripheral artery disease (LE-PAD) represents an independent predictor of worse outcome. However, the molecular mechanisms underlying these effects are currently unknown. Methods and results: To investigate these processes, we used in vitro approaches and several mouse models: (i) unilateral limb ischaemia by left common femoral artery ligation [peripheral ischaemia (PI), n = 38]; (ii) myocardial infarction by permanent ligation of the left descending coronary artery (MI, n = 40); (iii) MI after 5 weeks of limb ischaemia (PI + MI, n = 44); (iv) sham operation (SHAM, n = 20). Compared with MI, PI + MI hearts were characterized by a significant increase in cardiomyocyte apoptosis, larger infarct areas, and decreased cardiac function. By using a proteomic approach, we identified a ≅8 kDa circulating peptide, Dermcidin (DCD), secreted by ischaemic skeletal muscles, enhancing cardiomyocytes apoptosis under hypoxic conditions and infarct size after permanent coronary artery ligation. siRNA interference experiments to reduce DCD circulating levels significantly reduced infarct size and ameliorated cardiac function after MI. Conclusion: Our data demonstrate that chronic limb ischaemia activates detrimental pathways in the ischaemic heart through humoral mechanisms of remote organ crosstalk. Thus, DCD may represent a novel important myokine modulating cardiomyocyte survival and function.